The Association between Daily Level of Fine and Coarse Particles and Mortality in Seoul from 2006 to 2015 - 나원웅 (The Graduate School, Ajou University, 2019)
The most concerning environmental problem in Korea is particulate matter (PM) pollution. To solve this problem, the government has implemented various policies, such as strengthening the management standards of PM2.5 (which is PM of less than 2.5 μm in diameter; fine particle). However, the Public's concern is ongoing due to the excessive policies and inaccurate information from the media. In addition, PM management is focused on fine particles, whereas the health impact is more in case of PM with larger diameter (2.5–10 μm; PM2.5-10, coarse particle). However, there is a relative lack of information about the characteristics and health effects of coarse particles. Therefore, this study was conducted to examine the nature and occurrence of fine and coarse particles, and to determine the health effect of PM per size, in order to increase the understanding of fine dust and to propose a preferred management policy. The PM10 and fine particle data from 2006 to 2015, provided by Seoul Atmospheric Environment information site and climate environment headquarters, respectively, were used to examine the patterns of occurrence of coarse and fine particles. In addition, the meteorological data provided by the Meteorological Office was used to determine the nature of the occurrence of coarse and fine particles due to the meteorological factors. Health effects were estimated as the number of deaths by causes per day during the same period in Seoul by using the causes of death data. The causes of death in this study are non-traumatic, which include total deaths except for those from trauma and exogenous factors, cardiocerebrovascular disease, and respiratory causes. Generalized additive model assuming a Poisson distribution was used for statistical analysis, and five lag models (from lag 0 day to lag 4 days) were compared. From 2006 to 2015, the average PM10, PM2.5, and PM2.5-10 were 50.32, 25.44, and 24.88 μg/m3, respectively. Each average concentration was gradually reduced over 10 years, and the pattern of occurrence was different according to the season and weather conditions. The impact of PM2.5 on health was more significant than that of PM2.5-10. PM2.5-10 was associated with increment of 0.15% in non-traumatic deaths in lag 3 days per 10 μg/m3 increments. 10 μg/m3 increment of PM2.5 was associated with 0.30% of non-traumatic deaths in lag 2 days. Although deaths due to cardiocerebrovascular disease were likely to have association with increment of PM2.5, the relative risks were not significant. Respiratory deaths increased significantly to 0.64% on the second day when the PM2.5-10 was increased. In the analysis of impact of fine particles fraction on mortality, 10% increments in fine particle fraction were associated with 0.52% increment in non-traumatic death in lag 2 days. The concentration of PM2.5 should be managed intensively because of its high health impacts. However, because coarse particles also increase non-traumatic and respiratory disease deaths significantly, it is important to reduce their concentration and prevent the health impact.
학위논문(박사)--아주대학교 일반대학원 :의학과,2019. 2